Using patent information to identify innovative solutions for respiratory disease prevention in the mining sector - Gandon, Luiz Fernando Martins; Ferraz, Renato Ribeiro Nogueira; Quoniam, Luc; Reymond, David (Revista de Administração da UFSM, 2020)
Brazil ranks 4th in the world for occupational accidents. There are more than 700 thousand occurrences per year, which cost the country about R$10 billion. The objective of this study is to identify technologies, related to the prevention of occupational accidents and diseases, that are not protected in Brazil. We used Patent2net, a computational data mining tool, to evaluate worldwide patents deposited in the Espacenet database. Employing a technometric research approach, a Patent2net case study was carried out by analyzing over 1,600 occupational safety and/or occupational disease patents deposited in Espacenet. Notably, a Chinese utility model patent describing a helmet with a breathing mask, that provides the worker protection against the inhalation of chemical agents and head overheating. The technology described in the patent could be potentially replicated in Brazil, and utilized in the prevention against respiratory problems commonly diagnosed in miners, such as pneumoconiosis. This disease, in particular, requires compulsory notification and the treatment, under responsibility of the public health system, is costly to the country. Identifying technologies that could potentially reduce the number of work-related incidents and, in turn, lower the associated costs.